A cross-sectional study of teachers’ and students’ preferences for educational methods in the post-COVID-19 era - Akbari, Elham (Frontiers in Education, 2025)
IntroductionEducational paradigms and methods have evolved in recent years, particularly after the COVID-19 pandemic. The present study aimed to investigate teachers’ and students’ preferences for face-to-face, blended, and e-learning educational methods in the post-COVID-19 era. This study aims to investigate the attitudes of teachers and students toward three educational methods: face-to-face education, blended learning and e-learning.MethodsThe statistical population consisted of all teachers and students in Iran. The questionnaire was sent to them through the Shad system and Telegram. 9,395 students and 964 teachers voluntarily answered the questionnaires.Results and discussionThe results of the present study showed that both teachers and students, despite having a positive attitude towards new educational approaches, still preferred face-to-face education to blended and e-learning. Another part of the results showed that students in vocational schools preferred blended and e-learning more than other high school students. Also, students with an experience of academic failure and students who had lower incomes preferred e-learning and blended learning over face-to-face education. Students with higher incomes were also less likely to attend face-to-face education. Also, teachers with diploma and doctorate degrees were more inclined to e-learning and blended learning methods, and less teaching experience also strengthened this inclination. As to the teachers’ teaching level, the results showed that there was no significant relationship between the teaching level and the preferences of blended and face-to-face learning methods. However, primary school teachers were less inclined to e-learning than the teachers in the first and second years of the secondary school. Furthermore, the results indicated that teachers in prosperous areas had more preference for e-learning, than teachers in the poor and relatively poor areas. The findings of this study can help educational policymakers and authorities design and implement educational programs tailored to the preferences of teachers and students in the post-COVID-19 era.